2019
DOI: 10.1155/2019/8962730
|View full text |Cite
|
Sign up to set email alerts
|

Bone Augmentation of Peri-Implant Dehiscence Defects Using Multilaminated Small Intestinal Submucosa as a Barrier Membrane: An Experimental Study in Dogs

Abstract: Objective. The aim of the study is to evaluate the effects of multilaminated small intestinal submucosa (mSIS) combined with bone substitute material to repair peri-implant defects during guided bone regeneration procedures. Methods. Twelve implants were placed in bilateral lower premolars of three beagle dogs, and a peri-implant buccal bone defect (3 mm width and 4 mm height) was created at each implant site. A total of 12 sites were filled with a particulate bone substitute material and then randomly divided… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 27 publications
(38 reference statements)
1
4
0
Order By: Relevance
“…All parameters differed significantly from the control group, which was left empty. This study confirmed that the mSIS membrane applied with a bone graft could produce bone regeneration similar to collagen membranes 44 . The study design and comparison of the effect of membranes on BIC are similar to our study.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…All parameters differed significantly from the control group, which was left empty. This study confirmed that the mSIS membrane applied with a bone graft could produce bone regeneration similar to collagen membranes 44 . The study design and comparison of the effect of membranes on BIC are similar to our study.…”
Section: Discussionsupporting
confidence: 88%
“…This study confirmed that the mSIS membrane applied with a bone graft could produce bone regeneration similar to collagen membranes. 44 The study design and comparison of the effect of membranes on BIC are similar to our study. However, in our study, the effects of collagen membranes on BIC between each other were compared.…”
Section: Discussionmentioning
confidence: 77%
“…A common approach to enhance the mechanical properties of SIS membranes is to increase the number of layers of the SIS membrane. In a study of SIS membranes as guide bone regeneration (GBR) membranes for peri-implant dehiscence defects in beagle dogs, the 8-layer cell-free SIS membrane not only had superior mechanical properties over collagen membranes when wet, but also exhibited collagen membrane-like ways to enhance bone regeneration of peri-implant defects [ 90 ]. In another study, 2- and 4-layer SIS membranes were used as tissue-engineered heart valves for valve replacement in juvenile non-human primates.…”
Section: Sis Modificationmentioning
confidence: 99%
“…(2) NCCM: Twenty-two studies described NCCM complications. Nineteen studies reported that the animals healed well after surgery, with no significant inflammatory response observed and no signs of infection, wound dehiscence, or membrane exposure [32,34,42,43,46,65,67,73,79,80,86,88,92,95,96,99,100,103]. Two studies reported a chronic inflammatory response [34,60].…”
Section: (B) Membrane Degradation (1) Two-by-two Comparisonmentioning
confidence: 99%